Knowledge, attitude and practice of health professionals about probiotic use in Ahmedabad, India. Issue 1 (12th February 2018) - Soni, Richa; Tank, Kamna; Jain, Nayan
Abstract : Purpose: The purpose of this study was to assess the knowledge, attitude and practice about probiotic use among health professionals of Ahmedabad, India. Design/methodology/approach: A structured questionnaire was prepared. The questionnaire consisted of 12 close-ended questions related to definition, mechanism of action, safety consideration, health benefits, sources and four questions to assess their attitude and practice about probiotics. Total 267 healthcare professionals were requested to fill the questionnaire. Participants were doctors, medical students, nutritionists, nutrition students, pharmacists and pharmacy students. Findings: Results of the survey revealed that most of the participants (93.25 per cent) were aware of the term probiotic, 66.66 per cent professionals were able to answer the right mechanism of action of probiotics. Only 54.68 per cent health professionals knew the health benefits correctly. There was a significant difference between the knowledge of professionals from different fields ( p < 0.05). Medical students had highest knowledge scores, whereas nutrition students had lowest knowledge scores. There was no significant difference between knowledge of doctors, pharmacist and nutritionist, but knowledge of medical students was significantly higher than the nutrition students ( p < 0.05). Majority of the respondents (85.76 per cent) believed that probiotics are useful for patients. Nearly 50 per cent preferred probiotic food over probiotic drugs. Almost half of them (48.68 per cent) agreed that probiotics can significantly affect the outcome of any therapy. Originality/value: Nutritionists and medical students have shown to be more knowledgeable about probiotics than professionals and students of other fields. A positive and significant correlation was found between knowledge and attitude of healthcare providers.